PENGARUH PENGETAHUAN PAJAK, DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK - Nida Putri Rahmayanti; Rizky Mega Arini; Susmita Dian Indiraswari; Rifdah Riyan Dara (Al-Kalam Jurnal Komunikasi, Manajemen dan Bisnis, 2023)
This study aims to determine the effect of tax knowledge and tax sanctions on taxpayer compliance. The results showed that tax knowledge had an effect on taxpayer compliance, and tax sanctions also had an effect on taxpayer compliance. This proves how important knowledge of taxation is so that taxpayers understand how the rules, calculations and reporting of taxation. In addition, tax sanctions are also important to provide a deterrent effect on taxpayers who are not disciplined in paying taxes.